A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran - Ghahari, Hassan; Borowiec, Lech (Zootaxa, 2017)
The fauna of Iranian Bruchinae (Coleoptera: Chrysomelidae) is summarized in this paper. In total 117 species from 14 genera (Spermophagus Schoenherr, Zabrotes Horn, Acanthobruchidius Borowiec, Acanthoscelides Schilsky, Bruchidius Schilsky, Callosobruchus Pic, Mimosestes Bridwell, Paleoacanthoscelides Borowiec, Palaeobruchidius Egorov, Specularius Bridwell, Stator Bridwell, Bruchus Linnaeus, Caryedon Schoenherr, Rhaebus Fischer von Waldheim) are listed as the fauna of Iran.